CORRELATION AND PATH ANALYSIS IN RICE (Oryza sativa L.) FOR GRAIN YIELD AND ITS COMPONENTS - and K. N. YAMINI, T. SOUJANYA , V. HEMALATHA, P. REVATHI M. SRINIVAS PRASAD (The Journal of Research, PJTSAU, 2021)
Rice (Oryza sativa L.) is the major staple food crop for more than half of the world’s population and plays a pivotal role in food and nutritional security by providing 43 percent of the calorie requirement. In the coming decades, demand for rice is expected to keep intensifying along with the growing population. India is the second-most densely populated country and hence the prime objective of plant breeders would always be an improvement in the productivity of the economic product. In rice, grain yield is the ultimate criterion for developing a high yielding variety. However, straight selection for grain yield alone remains ineffective since it is a complex trait and influenced by many component characters. The rapid improvement in grain yield is possible only when selection is practiced for component traits also for which knowledge on inter relationship of plant characters with yield and among them is essential. Therefore, in the current study correlation analysis was carried out for understanding the nature of association between grain yield and its component traits.